Nutrition for the prevention and treatment of injuries in track and field athletes - Close, G. L.; Sale, C.; Baar, K.; Bermon, S. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
In athletics, the epidemiology of injuries occurring before or during an international elite competition has been extensively described (Edouard et al., 2015, 2016; Feddermann-Demont et al., 2014). Unfortunately, there is less accurate information available when it comes to injuries occurring during training (out of competition) periods and/or in subelite or recreational athletes. In elite track and field athletes, there were approximately 81 injuries per 1,000 athletes registered to a World Championship (Feddermann-Demont et al., 2014), in other words, approximately one in 12 registered athletes will incur injury during International Athletics Championships. This is important since approximately half of these injuries will result in a time loss and absence from sports, including both training and competing (Feddermann-Demont et al., 2014). Among these injuries, skeletal muscle is the principal type, accounting for 40.9% of all recorded injuries (Edouard et al., 2016), with 58% of these injuries resulting in time loss during the International Athletics Championships between 2007 and 2015. Hamstring injury is by far the most frequent injury (approximately 17%), and it is more frequent (relative risk: 1.94) in male athletes than in female athletes. These hamstring injuries are more frequently described in sprinters, whereas overuse injuries of the lower legs are more frequently reported in middle-long distance runners and race walkers. Elite female athletes experience more (relative risk: 3.1) stress fracture injuries than male athletes (Edouard et al., 2015), and this is explained by a higher incidence of Relative Energy Deficiency in Sport Syndrome (Mountjoy et al., 2014) and the associated reduced calcium absorption, fixation, and bone mineral density in this population.